Epidemiological, clinical, radiographic characterization of non‐syndromic supernumerary teeth in Chinese children and adolescents. (2nd November 2020) - Ma, Xiaowei; Jiang, Yue; Ge, Han; Yao, Yuan; Wang, Yanling; Mei, Yufeng; Wang, Dongmiao
Abstract: Objective: This retrospective study was purposed to evaluate epidemiological, clinical, and 3D radiological features of supernumerary teeth (ST) in a non‐syndromic Chinese children and adolescent dental population. Materials and Methods: Original cone‐beam CT (CBCT) data from 18, 861 patients aged from 6 to 17 years with dental maxillofacial diseases treated in a Chinese dental hospital from June 2012 to December 2018 were utilized to screen patients with ST. Diagnosis and characterizations of ST were analyzed by CBCT coupled with 3D reconstruction. All relevant epidemiological, clinical, and radiographic details about ST were collected and statistically analyzed. Results: Among total 18, 861 patients, 2, 768 ST were identified in 1984 subjects with a prevalence of 10.52% and a male:female ratio of 1.86:1. Majority of ST were single, conical, inverted, impacted, and located in maxilla anterior region. ST‐associated complications mainly included malposition, rotation, and impaction of adjacent teeth, which were notably associated with morphology and position of ST. Conclusion: The prevalence of ST in Chinese children and adolescent dental population was 10.52% and tended to present as single, conical, inverted, and impacted, which resulted in abnormalities of neighboring teeth. Our outcomes are beneficial for clinicians to more comprehensively understand the incidence, characterization, and clinical treatment planning of ST in dental children and adolescents.